Susceptibility of Clinical Enterobacterales Isolates With Common and Rare Carbapenemases to Mecillinam - Fuchs, Frieder; Ahmadzada, Aysel; Plambeck, Lars; Wille, Thorsten; Hamprecht, Axel (Frontiers in Microbiology, 2021)
Purpose: To investigate the susceptibility of carbapenemase-producing Enterobacterales (CPE) to mecillinam based on the recently updated European Committee on Antimicrobial Susceptibility Testing (EUCAST) breakpoints for uncomplicated Urinary Tract Infection (uUTI). Methods: The challenge collection consisted of 105 molecularly characterized Enterobacterales [Klebsiella spp. (N = 49), Escherichia coli (N = 30), Enterobacter cloacae (n = 13), Citrobacter freundii (N = 9), Proteus mirabilis (N = 3), and Raoultella ornithinolytica (N = 1)]. Isolates produced OXA-48 (N = 18), OXA-48-like (N = 18), VIM (N = 22), NDM (N = 22), KPC (N = 12), IMI (N = 9), IMP (N = 6), GES (N = 1), OXA-58 (N = 2) or combinations thereof (N = 5). MICs of carbapenems were determined by agar gradient diffusion (AGD). MICs of mecillinam were assessed by agar dilution (reference method) and compared to disk diffusion (DD) and AGD. Results: Overall 23/105 CPE (21.9%) were susceptible to mecillinam. Susceptibility was observed in E. coli (N = 12), E. cloacae (N = 7), and Klebsiella pneumoniae (N = 4) producing IMI, OXA-48, OXA-48-like, and NDM-1 carbapenemases. MIC50 for mecillinam in all isolates was 128 mg/L while MIC50 for meropenem was 8 mg/L. Lower MICs for mecillinam were found in IMI (MIC50 8 mg/L) and OXA-48-like (MIC50 16 mg/L) producers. The comparison of the different susceptibility methods showed very major errors of 12.2% with AGD and 8.5% with disk diffusion when compared to the reference method. Conclusion: Mecillinam susceptibility was restricted to isolates producing IMI-, OXA-48-like, and NDM-1 carbapenemases and was documented despite high carbapenem MICs in some isolates. Mecillinam could be a promising oral antimicrobial in uUTI caused by E. coli and E. cloacae isolates carrying IMI- and OXA-48-like carbapenemases; however, susceptibility testing by AGD and disk diffusion remains problematic.